2021
DOI: 10.3390/ijerph18147347
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Fossil Fuels in Japan’s National Energy Mix and Implications for Environmental Sustainability

Abstract: Despite the drive for increased environmental protection and the achievement of the Sustainable Development Goals (SDGs), coal, oil, and natural gas use continues to dominate Japan’s energy mix. In light of this issue, this research assessed the position of natural gas, oil, and coal energy use in Japan’s environmental mitigation efforts from the perspective of sustainable development with respect to economic growth between 1965 and 2019. In this regard, the study employs Bayer and Hanck cointegration, fully m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 92 publications
(140 reference statements)
3
29
0
Order By: Relevance
“…These trade activities have been possible through globalization. Globalization affects the process of production, which ultimately affects environmental quality [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…These trade activities have been possible through globalization. Globalization affects the process of production, which ultimately affects environmental quality [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates the need to find alternative clean, cheap, and reliable energy sources other than the current fossil fuels that dominate the global energy market. This has become even more necessary now than ever due to the negative effect that is associated with the use of fossil fuels on the environment [2][3][4][5][6][7][8]. It is estimated that the world's current primary energy consumption is made up of about 85% of non-renewable sources.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding energy sources, past studies have focused mainly on fossil fuel consumption, but interest has recently shifted to renewable energy sources, which are seeing increasing use [ 50 ]. Many studies have confirmed that increasing renewable energy intensity decreases carbon dioxide emissions [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 51 , 52 ].…”
Section: Literature Reviewmentioning
confidence: 99%